Votives, places and rituals in Etruscan religion
1 online resource (xliii, 291 pages)
Keywords: Etruscans were deemed “the most religious of men” by their Roman successors and it is hardly surprising that the topic of Etruscan religion has been explored for some time now. This volume offers a contribution to the continued study of Etruscan religion and daily life, by focusing on the less explored issue of ritual. Ritual is approached through fourteen case studies, considering mortuary customs, votive rituals and other religious and daily life practices. The book gathers new material, interpretations and approaches to the less emphasized areas of Etruscan religion, especially its votive aspects, based on archaeological and epigraphic sources.